A Comprehensive Review of the Direct Peptide Reactivity Assay in Skin Sensitization Testing: Applicability, Limitations, and Considerations - Omeragić, Elma; Imamović, Belma; Dedić, Mirza; Mujezin, Indira; Bečić, Ervina (Archives of Pharmacy, 2024)
Skin sensitization is a crucial endpoint in the safety assessment of chemicals, with the Direct Peptide Reactivity Assay (DPRA) emerging as a valuable in chemico method for evaluating a substance's sensitization potential. This review delves into the principles, applicability, and limitations of the DPRA within the context of the Adverse Outcome Pathway (AOP) framework for skin sensitization. We examine the DPRA's role in addressing the molecular initiating event of skin sensitization, its integration into Integrated Approaches to Testing and Assessment (IATA), and its performance in predicting sensitizers. The review also highlights the challenges in testing certain categories of chemicals and the importance of considering the DPRA's results alongside other complementary methods. By providing a comprehensive overview of the DPRA, this review aims to inform researchers, regulators, and clinicians about its utility and limitations in the context of skin sensitization testing.
Keywords: DPRA; in chemico method; skin sensitization